PENERAPAN PERTANYAAN HOTS UNTUK MENINGKATKAN MINAT MEMBACA DAN KEMAMPUAN LITERASI MEMBACA PADA SISWA KELAS V SEKOLAH DASAR DALAM MATA PELAJARAN BAHASA INDONESIA - Listia Manggi Asih; Dwi Heryanto; Supriyadi (ADISAM PUBLISHER, 2026)
This study aims to improve the reading literacy skills of grade V students through the application of HOTS questioning techniques in Indonesian language learning. The background of this study is the low understanding of students in reading and answering questions related to reading texts. The method used was classroom action research (PTK) consisting of two cycles. Each cycle includes planning, implementation, observation, and reflection. The research subjects were 32 grade V students of SD 001 Merdeka, with data collection techniques through observation, reading ability tests, and questionnaires. The results showed that the application of HOTS questions significantly improved students' reading literacy skills. The average pre-test score before the action was 65, while the post-test after cycle II increased to 80. In addition, students showed increased participation and active involvement during learning. The results of this study show that the HOTS questioning technique is effective in improving students' reading literacy. It is hoped that the results of this study can be a reference for teachers in applying interactive and interesting learning methods